What oat breeders really need from biotechnology? - Stuthman, Deon (MTT, 2004)
Various aspects of biotechnology have considerable potential to offer the oat improvement community. There are two principal criteria to judge the usefulness of any biotechnological approach: 1) do they address a critical need of oat breeders, and 2) are they cost effective. In the long term these must be satisfied to really make a contribution, novelty is not enough. There is considerable potential in borrowing from other species in terms of comparative genomics and in terms of adapting procedures which function well with other organisms. A complementing strategy among breeders and biotechnologists will best serve the oat improvement community.
Keywords: Ka; genetic variation; selection; directed variation; transformation; MAS; comparative genomics